On the Potential Effect of Increased Dietary Intake of Fruits and Vegetables on Biomarkers of Lipid Peroxidation in Type Diabetes Patients - Pincemail; N. Paquot; J. Cillard; I. Hininger; L. Iuliano; M. Cazaubiel; F. Guéraud; J.P. Chapelle; C. Kevers; C. Charlier; A. Albert; J.O. Defraigne (Journal of Pharmacy and Nutrition Sciences, 2013)
The present study was designed to test the hypothesis that an increased consumption of fruits and vegetables up to 600 g per day in type 2 diabetes patients can reduce oxidative damages to lipids. After a clinical examination, 29 type 2 diabetes patients were divided into two groups: the first one did not receive any special instructions about the diet while the second one received fruits and vegetables consumption advices thanks to a picture catalogue describing types of fruits and vegetables as well as quantities to be eaten every day. After two months of intervention, plasma concentrations in vitamin C, b-carotene and polyphenols remained unchanged in both groups when compared to baseline values. No significant decrease in lipid peroxidation as evidenced by nine biomarkers (malonaldehyde as TBAR’s, lipid peroxides, oxidized LDL, antibodies against oxidized LDL, isoprostanes, 7-keto-cholesterol, 7b-hydroxycholesterol, 4-hydroxynonenal metabolite, LDL size) was also noted. In conclusion, our findings confirmed the fact that the effect of high intake of fruits and vegetables on reducing oxidative damage to lipids remains largely controversial even in patients having an oxidative stress profile. Moreover, the present leaves open the question of the most appropriate markers of lipid peroxidation since only small correlations were evidenced between the large battery of tests investigated.